2005
DOI: 10.1007/s00467-005-2019-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of enteroviruses in renal biopsies from patients with immunoglobulin A nephropathy

Abstract: Viruses have been suspected to be one of the causes of IgA nephropathy (IgAN). Recent studies have detected viruses in renal tissues of patients with IgAN. Enteroviruses have been reported as pathogenic agents in some renal diseases. We previously reported that group B coxsackieviruses cause pathological changes in experimentally infected mouse kidney. The aim of the present study was to examine the participation of enteroviruses in the pathogenesis of renal diseases including IgAN. Renal biopsies of ten patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…The onset and exacerbations of IgAN are commonly preceded by infections, often affecting the upper respiratory tract, and various infectious agents have been investigated as possible triggers of IgAN (13-19). In particular, interest has focused on group A streptococcus (GAS; Streptococcus pyogenes ), a common cause of respiratory-tract infections, which expresses surface-located M proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The onset and exacerbations of IgAN are commonly preceded by infections, often affecting the upper respiratory tract, and various infectious agents have been investigated as possible triggers of IgAN (13-19). In particular, interest has focused on group A streptococcus (GAS; Streptococcus pyogenes ), a common cause of respiratory-tract infections, which expresses surface-located M proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Iwama et al (16) reported that Epstein-Barr virus (EBV)-specific DNA in renal biopsies was detected by PCR in seven (58%) of 12 patients with IgAN, three (50%) of six patients with membranous nephropathy, none (0%) of 10 patients with minor glomerular abnormalities, and two (100%) of two patients with focal segmental lesions. We reported positive PCR for the presence of enteroviral RNA for three of 10 patients with IgAN and that enteroviral infection may play a role in the mechanism of onset or evolution of IgAN (12).…”
Section: Discussionmentioning
confidence: 78%
“…Recently, viral antigens were detected in renal tissues from patients with IgAN and viral DNA by PCR or in situ hybridization (12)(13)(14)(15)(16). Enteroviruses are established or suspected causative agents in numerous diseases.…”
mentioning
confidence: 99%
“…In fact, kidney disease caused by enterovirus is not unusual, and a study on 10 patients with IgA nephropathy detected enterovirus in three out of 10 biopsies. 5 To our knowledge, this is the first case report of glomerulonephritis caused by CVA16.…”
Section: Discussionmentioning
confidence: 97%